2021
DOI: 10.3390/biology10121326
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Hepatic Assessment of Cineole and Its Derivatives in Common Brushtail Possums (Trichosurus vulpecula) and Rodents

Abstract: Folivore marsupials, such as brushtail possum (Trichosurus Vulpecula) and koala (Phascolarctos cinereus), can metabolise higher levels of dietary terpenes, such as cineole, that are toxic to eutherian mammals. While the highly efficient drug metabolising enzymes, cytochrome P450 3A (CYP3A) and phase II conjugating enzymes (UDP-glucuronosyltransferase, UGT), are involved in the metabolism of high levels of dietary terpenes, evidence for inhibitory actions on these enzymes by these terpenes is scant. Thus, this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 38 publications
(49 reference statements)
4
5
0
Order By: Relevance
“…This study found that possum had significantly higher basal UGT2B glucuronidation activity than avian (~8-fold). It should be noted that there are no previous reports in the literature of basal UGT2B glucuronidation activity in possums using p-nitrophenol glucuronidation, except for the study previously published by our research team [17]. In that study, possums had ~2-fold higher UGT catalytic activity compared to rodents, consistent with the findings of the present study.…”
Section: P-nitrophenol Glucuronidation Activitysupporting
confidence: 92%
See 3 more Smart Citations
“…This study found that possum had significantly higher basal UGT2B glucuronidation activity than avian (~8-fold). It should be noted that there are no previous reports in the literature of basal UGT2B glucuronidation activity in possums using p-nitrophenol glucuronidation, except for the study previously published by our research team [17]. In that study, possums had ~2-fold higher UGT catalytic activity compared to rodents, consistent with the findings of the present study.…”
Section: P-nitrophenol Glucuronidation Activitysupporting
confidence: 92%
“…Western blotting showed that CYP3A4 protein levels varied between the 4 species examined. Interestingly, possum liver had higher levels of hepatic CYP3A4 protein than avian (~4-fold), mouse (~2-fold), and human (~2-fold), similar to our previous study in possums and rodents [17]. The high CYP3A protein levels in possums could be due to the use of a mammalian CYP3A polyclonal antibody, which may have also detected other highly homologous isoforms of CYP3A in possums.…”
Section: Cyp3a Catalytic Activitysupporting
confidence: 86%
See 2 more Smart Citations
“…Recently, the reliability and robustness of the in silico methods for the assessment of CYP450 activities has increased substantially. Studies based on the implementation of web servers (Ekroos and Sjogren 2006) and molecular docking simulations (Chand et al 2021) have displayed good correlation with the in vitro results.…”
Section: Introductionmentioning
confidence: 90%